An examination of the development of Christian worship in the Southern Congo United Methodist Church with a view to promoting a relevant and indigenous form of worship - Nkonge, Jean-Marie (Rhodes University, Faculty of Divinity, Department of Divinity, 2001)
The scope of this thesis is the investigation of the nature and purpose of Christian worship with specific reference to its development in the Southern Congo United Methodist Church. The study combines three main sources of information - namely, the study of key theological concepts (chapter 3), the Holy Bible (chapter 4), and the investigation by questionnaires (chapter 6) - in order to address the issue of improving the worship and Christian life style for the contemporary Christian church within the Congolese context. Christian worship has been defined as a twofold event involving God's initiative in and through Jesus Christ, and men and women's response towards God's saving acts through the same Mediator, Jesus Christ. Seeing that the unchangeable Gospel relates to each culture, it is argued in this thesis that Congolese cultural values (local clergy, local languages, art forms, and other cultural elements) could be an integral part of worship. This long and slow process of incarnating the Christian message into the Congolese context could result in finding original and meaningful expressions of the Christian faith in the African context. Insights are drawn from the research to offer theological and pragmatic guidelines. In fact, it is suggested that the integration of Congolese cultural elements should be monitored by a Theological Commission at the congregational level, the district level, and the Annual Conference level. Furthermore, the last section of the last chapter provides helpful suggestions in dealing with practical issues with regard to the overall management of the Southern Congo United Methodist Church.
Keywords: Christianity; Christianity -- Congo; United Methodist Church -- Congo